Pengaruh Desan dan Harga Produk Sophie Martin Terhadap Keputusan Pembelian di Toko Sophieku Sragen - Yusmaneti Yusmaneti; Khabib Alia Akhmad; Indra Hastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The fashion industry is a sector that has experienced rapid growth in recent decades, marked by the emergence of various brands, both local and international. One well-known brand in Indonesia is Sophie Martin, known for offering a variety of fashion products with distinctive designs and competitive prices. This study was conducted with the aim of analyzing the extent to which product design and price factors influence consumer decisions in purchasing Sophie Martin products, especially at the Sophieku Sragen Store. This study used a quantitative approach with an associative nature, which aims to examine the relationship and influence between variables. Data were collected through a dare survey involving 96 female respondents who had previously made purchases at the Sophieku Sragen Store. These respondents were selected to ensure that the answers provided were truly based on real shopping experiences. The analytical method used was multiple linear regression, which allows researchers to assess the influence of each independent variable (product design and price) on the dependent variable (purchase decisions), both partially and simultaneously. The results of the analysis indicate that product design has a positive influence on purchasing decisions, where consumers tend to choose products with attractive, innovative, and trendy appearances. Price also has a positive influence, meaning consumers consider affordability and suitability to product quality before making a purchase. Simultaneously, these two variables significantly influence purchasing decisions. The coefficient of determination (R²) of 0.629 indicates that 62.9% of the variation in purchasing decisions can be explained by product design and price, while mortality is influenced by other factors not examined in this study, such as promotion, service quality, and brand image.